Addressing Underscreening for Cervical Cancer among South Asian Women: Using Concept Mapping to Compare Service Provider and Service User Perspectives of Cervical Screening in Ontario, Canada - Kimberly A. Devotta; Patricia O’Campo; Jacqueline L. Bender; Aisha K. Lofters (Current Oncology)
Cervical cancer is largely preventable through screening and treatment of cervical lesions. In the province of Ontario, South Asian women have some of the lowest rates of screening. The roles of service providers—those in healthcare and community services—and their interactions with screen-eligible people can greatly impact the uptake of screening. In our study, we used concept mapping (CM) to engage over 70 South Asian service users (i.e., those eligible for cervical screening) and service providers to identify a range of ideas and experiences that impact uptake of cervical screening for South Asian women, which were then rated by 45 participants in terms of ‘importance’ and ‘ease to address’ to encourage participation in cervical screening. Overall, ideas related to knowledge and education were rated as most important and easiest to address by both groups. Some differences were seen with South Asian service users valuing the importance of addressing ‘cultural beliefs and influences specific to sexual health’ more than service providers, while service providers valued the importance of addressing ‘lack of comfort and supportive relationships’ more than South Asian service users. Future interventions should target the knowledge and education needs of service users and increase service providers’ awareness of cultural beliefs and influences specific to sexual health.